Talking About Privilege: Framing Inequality as Advantage Is More Likely for Inequality in Positive Than in Negative Outcomes - Malapally, Annette; Bruckmüller, Susanne (Personality and social psychology bulletin, 2024)
Inequality is often one-sidedly framed as disadvantage, a practice identified as problematic by empirical research and critical scholarship, as it renders privilege invisible and shapes perceptions of and reactions to inequality. Importantly, inequality can mean differences in positive (e.g., promotions) or negative outcomes (e.g., harassment). Drawing on cognitive processes involved in (group) comparisons and the processing of positive and negative content, we predict that the valence of outcomes moderates the preference for disadvantage (vs. advantage) frames. We coded social media posts on gender inequality (Study 1, n = 1,402) and had participants in an online experiment (Study 2, n = 164) describe gender and sexual orientation inequality in positive and negative outcomes. Confirming hypotheses, people overall used disadvantage frames more, but were more likely to use advantage frames for inequality in positive (compared with negative) outcomes. We discuss theoretical implications for inequality framing research and practical implications for privilege awareness interventions.
CRIS-Team Scopus Importer:2024-09-06
Keywords: framing; inequality; privilege; social media; valence